General care of a patient: учебное пособие для использования в образовательных учреждениях, реализующих основные профессиональные образовательные программы высшего образования уровня специалитета по направлению подготовки 31.05.01 "Лечебное дело" - Ослопов, В. Н. терапия, кардиология 19451020 Владимир Николаевич (Tutorial, 2019)
Tutorial is compiled in accordance with the State Federal Educational Standard of Higher Education in 31.05.01 "General Medicine" speciality, the standard and working programs for the "General care" discipline. This tutorial highlights in details the content of unites, describes practical skills in a clear sequence of actions at the patient's bedside. The tutorial is intended for foreign students of medical higher education institutions.